Ferulic Acid Enhances Peripheral Nerve Regeneration across Long Gaps. (16th April 2013) - Lee, Sheng-Chi; Tsai, Chin-Chuan; Yao, Chun-Hsu; Chen, Yueh-Sheng; Wu, Ming-Chang
Abstract : This study investigated the effect of ferulic acid (FA) on peripheral nerve injury. In the in vitro test, the effect of FA on viability of Schwann cells was studied. In the in vivo test, right sciatic nerves of the rats were transected, and a 15 mm nerve defect was created. A nerve conduit made of silicone rubber tube filled with FA (5 and 25 μ g/mL), or saline (control), was implanted into the nerve defect. Results show that the number of proliferating Schwann cells increased significantly in the FA-treated group at 25 μ g/mL compared to that in the control group. After 8 weeks, the FA-treated group at 25 μ g/mL had a higher rate of successful regeneration across the wide gap, a significantly calcitonin gene-related peptide (CGRP) staining of the lamina I-II regions in the dorsal horn ipsilateral to the injury, a significantly diminished number of macrophages recruited, and a significantly shortening of the latency and an acceleration of the nerve conductive velocity (NCV) of the evoked muscle action potentials (MAPs) compared with the controls. In summary, the FA may be useful in the development of future strategies for the treatment of peripheral nerve injury.